Implementation of the Law. No. 23 of 2011 Concerning Zakat Management in the Empowered Program Through Z-Mart - El Muna, Naily; Zunaidi, Arif; Maupe, Masnur Daeng (Et-Tijarie, 2023)
The main problem in this study is that the use of productive zakat as a productive use of zakat is not optimal and the method of delivering zakat funds to mustahik to produce something continuously, with the zakat assets that he has received. Of several productive zakat utilization programs, one of them is Z-Mart. The Z-Mart program is an economic empowerment program in the form of the development of stalls/shops owned by mustahik. The purpose of this study is to find out the implementation of the Law. No. 23 of 2011 concerning Zakat Management in the Empowered Jombang Program Through Z-Mart contained in BAZNAS.The research method used is field research, with an empirical normative approach. Data collection by observation, interview, and documentation techniques. Data analysis is inductive by analyzing based on the data obtained and then developing certain relationship patterns.The result of this research is the utilization of productive zakat in the Z-Mart program with the implementation of Law. No. 23 of 2011 concerning Zakat Management in BAZNAS Jombang Regency is sufficient in implementing the articles contained in the Law related to collection, distribution, utilization, and reporting. The results of this study give implications that the birth of Law No. 23 of 2011 concerning Zakat Management strengthens the position of BAZNAS Jombang Regency can provide benefits in the management of productive zakat management that is more professional.